PENGEMBANGAN MODUL EDUKASI TERHADAP PERILAKU KECANDUAN GADGET (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: this study aims todevlope and Educational Module on GadgetAddiction Behavior. The type of research used is Research and Devlopment Resarchand Devlopment (R&D) To compile the perfect module in this study, a material expertvalidation test was carried out. The data collection technique in this study used aliterature review technique using validation intrument in the form of a questiannaireusing a likert scale. The result of this study, has been compiled learning modules witheducational material for gadget addiction behavior. The overall module valididationtest results are based on the material aspect, showing that the assesment scores88.31%, with the “ very feasible” category being used.Key Words: Module, Education, Gadget Addicition